TINJAUAN HUKUM PENYELESAIAN ATAS SENGKETA PERSAMAAN MEREK (STUDI PUTUSAN NOMOR 4/PDT.SUS.HKI/MEREK/2019/PN NIAGA MDN) - Prasetyo, Muhammad Arif; Talia, Dhea; Pangaribuan, Edo Rajaiman Martinus; Manurung, Fazri Siddik Sioloan (JURNAL DARMA AGUNG, 2022)
In managing a business, whether in the form of goods or services, everyone really needs a name or symbols to be used for the goods or services, which serve as a sign of where the goods or services come from. In Article 1 point (1) of Law No. 15 of 2001 juncto Law No. 20 of 2016 concerning Marks a definition of marks is given. With the development of a brand that makes a brand something so valuable, the legal protection of a mark also begins to develop and makes a mark a sign that is given ownership recognition. If it is related to Decision No. 4/Pdt.Sus.HKI/Merek/2019/PN Niaga Mdn, that is the similarity of the trademark between PT Pulau Ombak Indah as the plaintiff and Raihana Heuer as the defendant regarding the similarity of the trademark with the name Kandui Resort. Normative juridical is the research method used in this writing, namely analyzing the existing problem formulation and then correlating it with legal foundations based on regulations contained in a statutory regulation. Legal protection for a brand is strictly regulated through legal sanctions, both civil and even criminal in nature. This legal sanction is imposed on any person or legal entity that has been proven to have committed a trademark infringement. The imposition of legal sanctions is part of efforts to provide legal protection for legitimate brand owners. PT Pulau Ombak Indah is a legal entity that makes claims against the management of "KANDUI RESORT" which is a tourism industry located in the Mentawai area, West Sumatra where in this case the plaintiff filed a lawsuit against Raihana Heuer who is the holder of the KANDUI brand and Previously, KANDUI VILLAS, where the plaintiff felt that the defendant had registered the KANDUI brand based on bad faith, was because the defendant registered the mark secretly without the knowledge of the founder or management of KANDUI RESORT. However, in his decision the judge rejected the plaintiff's claim in its entirety.